Teacher Recruitment System: Case Study of Amanah Integrated Islamic Elementary School of Sungai Penuh City - Mulya Putra; Ismawati Ismawati; Muhammad Afifuddin Afandi (Sustainable, 2022)
The Amanah Integrated Islamic Elementary School (SDIT) of Sungai Penuh City is one of the long-established private elementary schools in Sungai Penuh City. This school is a private Islamic elementary school that has an A accreditation in Sungai Penuh City. As an institution known for its high level of discipline and strict administration, in reality there is an imperfect recruitment system. This study aims to identify and describe the implementation of the teacher recruitment system at the Amanah Integrated Islamic Elementary School (SDIT) of Sungai Penuh City. The method used in this research is qualitative method. Collecting data in this study are interviews, observation and study of documents. The data analysis technique used is by condensing data, presenting data and drawing conclusions. The results of the study showed that the teacher recruitment system implemented by the Amanah Integrated Islamic Elementary School (SDIT) of Sungai Penuh City was quite good.